ENVIRONMENTALLY FRIENDLY WATER TREATMENT TECHNOLOGY AT THERMAL POWER PLANTS - Asretdinova, Mukhabbat; Asretdinova, Lobar (Educational Research in Universal Sciences, 2022)
Water determines the quality of life and is a strategic resource, whose value has been steadily increasing every year. Water reserves are becoming unfit for consumption due to the water scarcity in many regions of the world and the pollution of the environment. Therefore, there is a strong demand for the development of new, highly-efficient and cost-effective technologies in the field of water treatment with reduced pollution to the environment. This paper describes the working principle of the highly efficient and latest equipment named IBE "ECOTECH". The technological and environmental advantages of the IBE “ECOTECH” water treatment equipment are discussed. Further suggestions are given to develop and take advantage in power engineering.